1994
DOI: 10.1111/j.1365-2672.1994.tb03447.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of low levels of specific Salmonella species by fluorescent antibodies and flow cytometry

Abstract: The use of fluorescently-labelled monoclonal antibodies, with detection by multi-parameter flow cytometry, was investigated for the rapid detection of salmonellas in pure cultures. Accurate detection of specific Salmonella serotypes was demonstrated down to levels of below 10(4) cells ml-1 (within 30 min) and 1 cell ml-1 (after 6 h non-selective pre-enrichment). This level of sensitivity was attained even in the presence of high levels of other bacterial species that would otherwise have interfered with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 33 publications
(25 reference statements)
2
28
0
1
Order By: Relevance
“…Vesey et al, 1994). These were used to detect Legionella (Ingram et al, 1982;Tyndall et al, 1985), Bacillus (Philips and Martin, 1983), Salmonella typhimurium (McClelland and Pinder, 1994) and Listeria monocytogenes (Donnelly and Baigent, 1986), with detection limits as low as 20 cells ml -1 . Although some nonspecific identification can always occur, detection of 1 positive cell in a background of 10000 negative cells is possible.…”
Section: Phylogenetic Heterogeneitymentioning
confidence: 99%
“…Vesey et al, 1994). These were used to detect Legionella (Ingram et al, 1982;Tyndall et al, 1985), Bacillus (Philips and Martin, 1983), Salmonella typhimurium (McClelland and Pinder, 1994) and Listeria monocytogenes (Donnelly and Baigent, 1986), with detection limits as low as 20 cells ml -1 . Although some nonspecific identification can always occur, detection of 1 positive cell in a background of 10000 negative cells is possible.…”
Section: Phylogenetic Heterogeneitymentioning
confidence: 99%
“…The phycobiliproteins are almost exclusively used as immunofluorescent labels for eucaryotic cells, in particular lymphocytes, although they have also been applied in microbiology. In the study by McClelland and Pinder (77), R-PE labelled Salmonella typhimurium was discriminated from FITC-labelled Salmonella enteridis or Salmonella montevideo by flow cytometry. Porter et al (102) reported the recovery of Escherichia coli from sewage by R-PE labelled antirabbit IgG antibodies in an indirect immunoassay (i.e.…”
Section: Fluorescent Probesmentioning
confidence: 99%
“…In an early work from 1983, Groschel (122) explained somewhat prophetically the use of antibodies in clinical microbiology. FCM in conjunction with fluorescent antibodies has been used to detect surface antigens in Haemophilus (298), Salmonella (57,207), Mycobacterium (238), Brucella (35), Branhamella catarrhalis (29), Mycoplasma fermentans (50), Pseudomonas aeruginosa (134), Bacteroides fragilis (191,239) and Legionella (143), among other microorganisms. These examples illustrate the sensitivity and specificity of using antibodies that allow the detection of particular cell types (of as few as 100 cells per ml in 30 min) in heterogeneous populations (57).…”
Section: Direct Detectionmentioning
confidence: 99%